2013
DOI: 10.1007/s00268-013-1904-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hemangioma of the Liver: Surgical Therapy or Observation?

Abstract: The majority of patients with liver hemangioma can be safely managed by clinical observation. In a subset of patients, especially those with giant hemangioma and/or occurrence of symptoms, surgical treatment could be considered and is justified in high-volume centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 52 publications
0
40
0
3
Order By: Relevance
“…Recent recommendations indicate that patients with hemangiomas smaller than 4 cm and without any symptoms should be kept under observation only. 7 Although surgical treatment is the classic method for symptomatic giant hemangioma, some studies have evaluated the effects of embolization with bleomycin mixed with lipiodol for ameliorating symptoms and inducing size reduction. 8 Because surgical treatment for giant liver hemangioma has morbidity rates similar to those obtained in patients followed up without treatment, it has been argued that liver resection should be reserved for patients with severe symptoms or diseaseassociated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent recommendations indicate that patients with hemangiomas smaller than 4 cm and without any symptoms should be kept under observation only. 7 Although surgical treatment is the classic method for symptomatic giant hemangioma, some studies have evaluated the effects of embolization with bleomycin mixed with lipiodol for ameliorating symptoms and inducing size reduction. 8 Because surgical treatment for giant liver hemangioma has morbidity rates similar to those obtained in patients followed up without treatment, it has been argued that liver resection should be reserved for patients with severe symptoms or diseaseassociated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency surgery for complicated liver hemangiomas is seldom necessary, since bleeding, spontaneous rupture, and tumor thrombosis have been exceptionally reported [ 32 ].…”
Section: Indications For Surgerymentioning
confidence: 99%
“…Some authors prefer enucleation for the following reasons: there is a dissection plane between the hemangioma and the liver NR not reported parenchyma, and ligation of the transversing vessels is much simpler, decreasing the risk of blood loss; there are no bile ducts in the enucleation dissection plane so that the risk of postoperative bile leak is minimal; enucleation avoids unnecessary loss of healthy parenchyma for the treatment of a benign lesion [ 28 , 31 ]. While some authors report fewer intra-abdominal complications after enucleation than after hepatectomy [ 27 ], others prefer anatomic liver resections [ 32 ]. In the case of enucleation, the centrally located hemangiomas are more likely to be associated to longer operative time and higher blood losses and transfusion rates, compared to peripherally located tumors [ 36 ].…”
Section: Surgical Techniquementioning
confidence: 99%
“…The indications of surgery for giant liver hemangioma is well defined and symptomatic or complicated lesions are the most conditions requiring surgical management [4,13,18,[29][30][31]. Combined use of advanced various imaging techniques allows to establish diagnostic certainty in most cases.…”
Section: Surgical Approachmentioning
confidence: 99%
“…The published studies assessing observation of giant liver hemangiomas demonstrated that health status and quality of life of observed patients varied from good to excellent concluding that observation was safe in most patients [11]. Conservative approach is justified even in very large hemangiomas and tumour size alone is not supported as an indication for urgery [12][13][14][15][16][17]. Thus, asymptomatic and non-complicated giant liver hemangioma can be safely observed by supervision through regular imaging control with lower risk of adverse events [2,[15][16][17][18][19][20][21].…”
Section: Observational Approachmentioning
confidence: 99%